A review on entropy generation in natural and mixed convection heat transfer for energy systems - Öztop, Hakan Fehmi; Al-Salem, Khaled (Pergamon-Elsevier Science Ltd, 2012)
This paper reviews the second law analysis of thermodynamics in enclosures due to buoyancy-induced flow for energy systems. It defines entropy generation minimization or thermodynamic optimization. In addition, the article summarizes the recent works on entropy generation in buoyancy-induced flows in cavity and channels. Studies on mixed convection were also included in the study. Presentation was performed for flow in porous media and viscous fluid filled media at different shaped enclosures and duct under buoyancy-induced force. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Entropy generation; Energy; Thermodynamics; Natural convection; Mixed convection